Exploring the need to incorporate the right to environment into international law - Kowalski, Jarosław; Kowalska, Aleksandra (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2024)
It is necessary to promote green growth in times of climate crisis. The realization of human rights, in particular the right to environment, fosters sustainable development. The article aims to justify the need to include the right to environment in United Nations (UN) legal acts and regional human rights protection systems. The methodological approach involved conducting a narrative literature review to investigate the issue. A well-established and effective regional system for the protection of the human right to environment would strengthen the respect for this right at the national level. The complexity of the UN creates an obstacle to the exercise of this right, as concluding agreements among States at different stages of development is very difficult. However, incorporating the human right to environment into UN legal acts could give momentum to including this right in national legislation. Building a comprehensive and coherent legislative framework for the protection of the human right to environment at global, regional and national levels should contribute to the improvement of the ecosystem and human health, which is key to sustainable development.